Causes Of Consumptive Behavior Of Housewives In The Phenomenon Of National Online Shopping Day (Harbolnas) (Case Study Of Parents Of Students At Sdn 060 Raya Barat Bandung, Indonesia) - Sopiani, Siti Sopia; Nurdin, Muhamad Fadhil; Fedryansyah , Muhammad (International Journal of Science and Society, 2024)
The phenomenon of harbolnas is still an interesting issue to discuss. Harbolnas is an annual activity jointly initiated by six major e-commerce companies in Indonesia since December 12, 2012, which is National Online Shopping Day in Indonesia. The development of online shopping media is in line with the increasing consumptive nature in society, especially for women who are targeted. This can make "shopping freak" consumptive behavior even more so. The subject of this study is housewives who have a role in "financial management" but have a consumptive attitude during harbolnas. This is because the goods offered are cheaper and more practical when shopping with the services that are presented more easily in the online shop, encouraging housewives to make it an alternative place to shop. The theory used is the Theory of Rational Choice (James S. Coleman). Data collection is carried out by conducting interviews, observations, and literature studies to analyze several documents (articles) and literature related to existing issues as a basic basis for researchers to formulate existing reality. The results of this study show that the causes of consumptive behavior are influenced by internal and external factors. It is known that internal factors from 1) the Encouragement of Needs and Motivation (Self-Will), 2) Interest Only (Purchase Impulsively), 3) the Harbolnas discount program, 4) the existence of free shipping, and 5) the existence of advertisements on television or social media when Harbolnas. External factors that influence are 1) Reference Groups (Friendship), 2) groups in shopping (Shopping Groups), and 3) Family.